Penguatan Soft Skills Mahasiswa Generasi Z Melalui Pelatihan Master of Ceremony Berbasis Experiential Learning - Mar’atus Sholikah; Anni Safitri (Jaanur ElBarik Indonesia, 2026)
This Community Service (PkM) activity will implement an experiential learning-based Master of Ceremony (MC) training model. This PkM is conducted through the stages of needs analysis, practical simulation implementation, and evaluation using pretest-posttest instruments. There were 33 students in attendance. The results of this PkM activity found a significant increase in self-confidence, verbal and nonverbal communication, improvisation, and audience management. The results of this PkM also prove that the experiential learning approach is effective in improving master of ceremonies skills through direct practice and structured reflection